Victims' State : War and Welfare in Austria, 1868-1925 - Hsia, Ke-Chin (Book collections on Project MUSE., 2022)
"This book offers the first integrated account about how late Imperial Austria and the First Austrian Republic responded to the needs of soldiers and their families when they faced adverse consequences of soldiering. It surveys the evolving legal and institutional context from the 19th century to the interwar years as well as the concrete actions taken by public and societal actors in confronting the massive losses in lives, health, and livelihoods during and after the First World War, specifically on the provision of care and welfare for disabled soldiers and dead soldiers' widows and orphans. Straddling the conventional historiographical divide of 1918, this book argues that the revolutions of 1918 was not all-determining in the realm of social policy and welfare politics in the post-Habsburg Central Europe. Rather, a "social offensive on the home front" was already initiated in 1917 and gained fresh momentum in 1918 and 1919 thanks to the emergence of war victims themselves as an assertive social movement that the new Austrian Republic sought to court and even partner with. This pivotal period in the Austrian warfare-welfare nexus is part of the longer trajectory of how the Austrian state became self-consciously "social" in the age of democratizing mass politics and mass conscription. It is also a story about war and war victim welfare's key roles in the formation of modern Austrian citizenship and statehood"--